THE ROLE OF READING IN RAISING THE MORALE OF STUDENTS AND GIRLS - Kuchkarova Oysha Oltibayevna (Journals Park Publishing, 2022)
The role of a person in raising spirituality, the formation of a culture of reading among students and girls, the reading of a book leads a person to spiritual perfection, the formation of a person as a comprehensively mature, perfect person is incredibly incomparable. In particular, valuable information was given on such issues as human perfection, spiritual maturity, patriotism, education and training in the oral creativity of the people, views, ideas and works of Eastern thinkers.This paper presents some evidence and their theoretical framework for the formation of student girls‘spirituality, upbringing in the spirit of loyalty to our national and universal values.
Keywords: spirituality; spiritual wealth; youth